Clinical courses and predictors for rebleeding in patients with peptic ulcers and non-bleeding visible vessels: a prospective study. Issue 10 (October 1994) - Lin, H J; Perng, C L; Lee, F Y; Lee, C H; Lee, S D
Abstract : Detailed characterisation of non-bleeding visible vessels in terms of colour, size evolution, and time of rebleeding is important in determining the natural history of these lesions. The colour and size of non-bleeding visible vessels were observed endoscopically every day for three days and then every other day until rebleeding or flattening of visible vessels occurred in 140 patients. Rebleeding happened in 61 (44%) patients. Of them, 59 (97%) rebled within 72 hours. Flattening of visible vessels happened in 79 (56%) patients and 77 of 79 (98%) had flattening of visible vessels within 72 hours. Rebleeding rate increased with increasing length of exposed vessels (r = 0.96, p < 0.001). Coffee ground fluid or blood retention in the stomach and ulcer size > or = 2.0 cm were independent predictors for rebleeding using multivariate analysis. It is suggested that patients with non-bleeding visible vessels and independent predictors for rebleeding may need early aggressive treatment.